2018
DOI: 10.1016/j.bbrep.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Gut microbiota on Amygdalin and its use as an anti-cancer therapy: Substantial review on the key components involved in altering dose efficacy and toxicity

Abstract: Conventional and Alternative Medicine (CAM) is popularly used due to side-effects and failure of approved methods, for diseases like Epilepsy and Cancer. Amygdalin, a cyanogenic diglycoside is commonly administered for cancer with other CAM therapies like vitamins and seeds of fruits like apricots and bitter almonds, due to its ability to hydrolyse to hydrogen cyanide (HCN), benzaldehyde and glucose. Over the years, several cases of cyanide toxicity on ingestion have been documented. In-vitro and in-vivo studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 77 publications
(99 reference statements)
0
47
0
Order By: Relevance
“…This result indicated that the toxicity of amygdalin was likely to depend on the microorganisms in the intestine. And then Jaswal et al found that the amount of hydrogen cyanide (HCN) produced by different intestinal microbes hydrolyzing amygdalin was different. Probiotic consumption, obesity, diet, age, etc all can change the distribution of intestinal microecology, which affects the production of HCN in human body.…”
Section: Current Status Of Clinical Research On Amygdalinmentioning
confidence: 99%
“…This result indicated that the toxicity of amygdalin was likely to depend on the microorganisms in the intestine. And then Jaswal et al found that the amount of hydrogen cyanide (HCN) produced by different intestinal microbes hydrolyzing amygdalin was different. Probiotic consumption, obesity, diet, age, etc all can change the distribution of intestinal microecology, which affects the production of HCN in human body.…”
Section: Current Status Of Clinical Research On Amygdalinmentioning
confidence: 99%
“…In addition, gut microbiota can increase the toxicity of several THM, such as amygdalin, hydrolyze this to HCN under the anaerobic Bacteroidetes phylum in the gut and cause toxicity. 193 In summary, both historic and modern science validate the efficacy of THM, however research and development in this eld has staggered due to the complexity of ingredients and the unknown mechanism of action. Thus, in recent years, research on gut microbiota has brought a new perspective into the study of THM.…”
Section: Perspectivesmentioning
confidence: 99%
“…In addition, the cyanide content in bitter almond decreased with increasing temperature at the same boiling time. The result was explained as follows: the glycosidase activity was activated with increasing temperature over a range of temperatures, which facilitated the conversion of the amygdalin into HCN (Yu et al, 2005;Jaswal et al, 2018). The formed HCN was rapidly volatilised due to its low boiling point (25.7-26.5°C) (Khare et al, 1994).…”
Section: Water Boiling Treatmentmentioning
confidence: 99%